Implementation Of The Tpsr Model And Jigsaw Type Cooperative Model In Technical Management Learning To Improve Student's Social Skills - Raesi Saeful Azhar; Tatang Muhtar; Yudha Munajat Saputra (STKIP Muhammadiyah Kuningan, 2022)
The physical education learning process, which is still oriented towards mastery of movement and achievement, makes teachers ignore other skills, one of which is social skills which are very important in the process of child development. This study aimed to examine the effect of the TPSR (Teaching, Personal, Social & Responsibility) and Cooperative jigsaw model on students' social skills. The method used in this research is a proper experimental design. The research population was all 5th-grade students at SDN 111 Pindad, Bandung City. The research sample used in class 5 was 60 students according to research needs. The data collection process was carried out pre and post with the social skills instrument (Social Skill Improvement System) developed by Gresham and Elliot. Based on the research results, the TPSR and cooperative models can improve students' social skills. However, in the independent sample T-test of the TPSR model and the jigsaw cooperative, there was no significant difference in improving social skills.